Report on the Syrian university, Damascus, Syria = Rapport succinct concernant l'université syrienne, Damas, Syrie. (S.l. : s.n., 1949)
Bibliotheek Camille Huysmans
Engels
Frans
Arabisch
Brochure
Keywords: universiteiten; Syrië